2009
DOI: 10.1002/apj.220
|View full text |Cite
|
Sign up to set email alerts
|

Wear of the artificial hip joint material under lubrication

Abstract: A study of wear properties of hip-replacement materials, namely high-nitrogen stainless-steel femoral heads and ultra-high molecular weight polyethylene (UHMWPE), was conducted in a non-conforming apparatus using various liquid lubricants. The liquids used were normal saline solution, sodium azide solution, pure ethanol, aqueous hyaluronic acid and aqueous hyaluronic acid/cholesterol and cholesterol palmitate liquid crystal lubricant. Saline solution proved to be unsuitable as a lubricant while sodium azide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The variation tendency and the correlation coefficients of the WRs of these composites were about −0.998 and −0.988 in the two lubrication conditions, respectively ( p < 0.05; Figure and Table ). Furthermore, it might have been related to the corrosion effect in NS that a much higher WR was found in the lubrication condition of NS than in those of DW . The damage caused by friction decreased because the stress was effectively transferred by the inorganic filler of GO, which was uniformly distributed in the UHMWPE matrix .…”
Section: Resultsmentioning
confidence: 99%
“…The variation tendency and the correlation coefficients of the WRs of these composites were about −0.998 and −0.988 in the two lubrication conditions, respectively ( p < 0.05; Figure and Table ). Furthermore, it might have been related to the corrosion effect in NS that a much higher WR was found in the lubrication condition of NS than in those of DW . The damage caused by friction decreased because the stress was effectively transferred by the inorganic filler of GO, which was uniformly distributed in the UHMWPE matrix .…”
Section: Resultsmentioning
confidence: 99%
“…Waters, et al [ 24 ] found that cholesterol palmitate liquid crystal lubricant significantly reduced wear and atomic force microscopy (AFM) showed that the liquid crystal formed protective layers on the counterface surfaces, high-nitrogen stainless-steel femoral heads and ultra-high molecular weight polyethylene (UHMWPE). It was concluded that a dramatic reduction in wear could be achieved by incorporation of liquid crystal lubricant in hip-replacement elements.…”
Section: Liquid Crystals In Tribologymentioning
confidence: 99%
“…example, Waters et al found that cholesteryl palmitate liquid crystal lubricants formed a protective layer on the surface of hip replacement materials and dramatically reduced wear. 17 However, studies rarely focused on both the lubrication effect and the dynamic drug release. Therefore, it is worthwhile to investigate the friction-reducing and antiwear properties of the drug-loaded liquid crystal system and the controlled release of drugs under dynamic conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, the lubrication performance of liquid crystals can be used for joint lubrication. For example, Waters et al found that cholesteryl palmitate liquid crystal lubricants formed a protective layer on the surface of hip replacement materials and dramatically reduced wear . However, studies rarely focused on both the lubrication effect and the dynamic drug release.…”
Section: Introductionmentioning
confidence: 99%